2016
DOI: 10.1083/jcb.201608019
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic exit: Determining the PP2A dephosphorylation program

Abstract: In mitotic exit, proteins that were highly phosphorylated are sequentially targeted by the phosphatase PP2A-B55, but what underlies substrate selection is unclear. In this issue, Cundell et al. (2016. J. Cell Biol. http://dx.doi.org/10.1083/jcb.201606033) identify the determinants of PP2A-B55’s dephosphorylation program, thereby influencing spindle disassembly, nuclear envelope reformation, and cytokinesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…The structural subunit (PR65/A: 65 kDa), the regulatory subunit (B subunit: 50~130 kDa) and the catalytic subunit (PP2Ac: 36 ~ 38 kDa) form a trimer; this complex, is involved in the cell cycle, DNA replication, signal transduction, cell differentiation, malignant transformation and other cellular and biological events. PP2A was traditionally considered to be related to the occurrence and development of neurodegenerative diseases, tumors and other diseases 11 - 13 . Aberrant PP2A expression is associated with the occurrence and development of many malignant tumors, such as colorectal cancer, breast cancer, lung cancer and glioma 14 - 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The structural subunit (PR65/A: 65 kDa), the regulatory subunit (B subunit: 50~130 kDa) and the catalytic subunit (PP2Ac: 36 ~ 38 kDa) form a trimer; this complex, is involved in the cell cycle, DNA replication, signal transduction, cell differentiation, malignant transformation and other cellular and biological events. PP2A was traditionally considered to be related to the occurrence and development of neurodegenerative diseases, tumors and other diseases 11 - 13 . Aberrant PP2A expression is associated with the occurrence and development of many malignant tumors, such as colorectal cancer, breast cancer, lung cancer and glioma 14 - 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Entry into and progression through mitosis are driven by the phosphorylation of thousands of substrates under the master control of various mitotic kinases, such as CDK1 and PLK1 21 . However, phosphatase activities rise to cooperate with the declining activities of mitotic kinases to reset the phosphorylation status of proteins to the general low level that is characteristic of G1-phase cells 22 . Studies on yeast and human cells have revealed a timely defined dephosphorylation program that coordinates and regulates events in anaphase, telophase, and cytokinesis 23 25 .…”
Section: Discussionmentioning
confidence: 99%
“…When the CENPF protein was increased, it prompted the production of AURKA kinase. Here, the rise of CDCA8 regulators will not only indirectly promote the production of AURKA kinase [14], but also directly affect it.…”
Section: Construction Of Cdtgrn Gene Regulatory Networkmentioning
confidence: 99%